PERAN RUMAH KREATIVITAS MAHASISWA ICD DALAM PEMBERDAYAAN MASYARAKAT Penyusunan Data Keagamaan Nagari Pasie Laweh - Irwandi, Irwandi; Maimori, Romi (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2022)
The development carried out in the Pasie Laweh village requires accurate data in the context of preparing future nagari activity programs. The compilation of religious data is associated with community empowerment in the form of compiling data on the potential of the nagari in the religious field which is carried out based on the results of the collaboration between the Islamic Creative House Community Development (ICD) Islamic Community Development Study Program (PMI) Faculty of Ushuluddin Adab and Da'wah IAIN Batusangkar with Nagari Pasie Laweh, Sungai Tarab District, Tanah Datar Regency. In the field of custom and culture, potential data in the economic sector, potential data in the Social Sector, Among the potentials mapped on the mapping of potential in the religious field, the method used in this research is based on the survey research method. Survey research is research that takes a sample from a population by using a questionnaire as a data collection tool. The data collection technique is carried out in the following way;observations, interviews, questionnaires, and documentation, the results obtained are the commitment of the nagari government in using data in preparing the nagari budget in the form of the nagari revenue and expenditure budget (APBNag).